One-time double-layer placement of controlled-release urea enhances wheat yield, nitrogen use efficiency and mitigates N2O emissions - Akhtar, Muhammad; Liuge, Wu; Jian, Chen; Yuxiao, Su; Yuntan, Zheng; Yulun, Lu; Shanchao, Zheng; Aixing, Deng; Zhenwei, Song; Chengyan, Zheng; Weijian, Zhang (Frontiers in Plant Science, 2025)
Simultaneously enhancing the crop yield and reducing nitrous oxide (N2O) emissions presents a critical challenge in sustainable agriculture. The application of nitrogen (N) fertilizer is a key strategy to enhance crop yield. However, conventional N application practices often lead to excessive soil N accumulation, insufficient crop N uptake and elevated greenhouse gas (GHG) emissions. To address these issues, this study evaluated the effectiveness of one-time double-layer fertilization of controlled-release urea (CRU) in improving wheat yield, nitrogen use efficiency (NUE) and mitigating N2O emissions compared to single-layer fertilization. A two-year field experiment (2021-2023) was conducted with five treatments: zero N fertilizer (T0), one-time single-layer fertilization of urea at 8–10 cm soil depth (T1), one-time single-layer fertilization of CRU at 8–10 cm soil depth (T2), one-time double-layer fertilization of urea at 8–10 cm & 18–20 cm soil depth (T3), one-time double-layer fertilization of CRU at 8–10 cm & 18–20 cm soil depth (T4). The two-year average results indicated that one-time double-layer fertilization of CRU (T4) achieved the highest wheat yield (10.20 t ha-1) and NUE (19.13 kg kg-1), as well as the lowest N2O emissions (0.66 kg ha-1). Compared to single-layer CRU fertilization (T2), T4 increased wheat yield and NUE by 5.94% and 11.26%, respectively, while reducing N2O emissions by 22.50%. Furthermore, T4 optimized the soil microenvironment by lowering soil temperature and NO3−-N content at 0–10 cm depth, while enhancing soil moisture and NH4+-N availability at 10–20 cm, thereby promoting plant N uptake and utilization. These findings suggest that the one-time double-layer fertilization of CRU synchronizes N release with crop demand and regulates soil N dynamics, offering a promising strategy to boost wheat productivity and minimize environmental impacts.